PK-PD Analysis of Marbofloxacin against Streptococcus suis in Pigs - Lei, Zhixin; Liu, Qianying; Yang, Bing; Khaliq, Haseeb; Cao, Jiyue; He, Qigai (Frontiers in Pharmacology, 2017)
Marbofloxacin is a fluoroquinolone antibiotic and highly effective treatment for respiratory diseases. Here we aimed to evaluate the ex vivo activity of marbofloxacin against Streptococcus suis in pig serum, as well as the optimal dosages scheme for avoiding the fluoroquinolone resistance development. A single dose of 8 mg/kg body weight (bw) was administrated orally to healthy pigs and serum samples were collected during the next 72 h. Serum marbofloxacin content was determined by high-performance liquid chromatography. We estimated the Cmax (6.28 μg/ml), AUC0-24 h (60.30 μg.h/ml), AUC0-∞ (88.94 μg.h/ml), T1/2ke, (12.48 h), Tmax (0.75 h) and Clb (0.104 L/h) of marbofloxacin in pigs, as well as the bioavailability of marbofloxacin (94.21%) after a single 8 mg/kg oral administration. We also determined the pharmacodynamic of marbofloxacin against 134 Streptococcus suis strains isolated from Chinese cities in TSB and serum. These isolated strains had a MIC90 of 1 μg/ml. HB2, a virulent, serotype 2 isolate of SS, was selected for having antibacterial activity in TSB and serum to marbofloxacin. We determined the minimum inhibitory concentration (MIC, 1 μg/ml in TSB, 2 μg/ml in serum), minimum bactericidal concentration (MBC, 4 μg/ml in TSB, 4 μg/ml in serum), and mutant prevention concentration (2.56 μg/ml in TSB) for marbofloxacin against Streptococcus suis (HB2). In serum, by inhibitory sigmoid Emax modeling, the AUC0-24h/MIC values for marbofloxacin against HB2 were 25.23 (bacteriostatic), 35.64 (bactericidal), and 39.71 (elimination) h. Based on Monte Carlo simulations, the predicted optimal oral doses of marbofloxacin curing Streptococcus suis were 5.88 (bacteriostatic), 8.34 (bactericidal), and 9.36 (elimination) mg/kg.bw for a 50% target attainment ratio, and 8.16 (bacteriostatic), 11.31 (bactericidal), and 12.35 (elimination) mg/kg.bw for a 90% target attainment ratio. The data presented here provides optimized dosage information for clinical use; however, these predicted dosages should also be validated in clinical practice.